What makes medical students choose their residencies? Association between mental health of medical students and their choices of future medical specialties - Natalia Karina Bartosik; Aleksandra Smolarek; Adrianna Frączek; Maria Dobielska; Marcin Kosmalski; Tadeusz Pietras; Adam Jóźwik (Nicolaus Copernicus University in Toruń, 2024)
Background: Excessive cognitive demands and chronic stress contribute to the occurrence of mental health problems among medical students. It may be hypothesized that the presence of such disturbances have an influence on their choices of post-graduate training programs. Objective: The aim of the study was to evaluate the state of mental health of medical students and to assess if there is any association between the prevalence of mental health problems and their residency choices. Materials and methods: 114 medical students were surveyed in terms of their residencies' choices and their mental health with the usage of validated psychological questionnaires. Results: 74 (64,91%) of medical students needed psychiatric or psychological treatment at some stage in their lives. Intensity of risky alcohol consumption was positively correlated with the choice of surgery (p=.0000) and negatively correlated with the choice of psychiatry (p=.0000). The severity of depressive symptoms was positively correlated with emergency medicine choice (p=.0479). Anxiety symptoms, eating disorders and autism spectrum severity symptoms were not significantly correlated with the choice of any medical specialty. Conclusions: Medical students were found seriously affected by mental health problems, what to some extent seemed to impact their future career choices.